Políticas públicas de transferência de renda: um estudo sobre o Programa Bolsa Família na favela do Pavão-Pavãozinho, Rio de Janeiro - Pinto, Michele de Lavra (2016)
Bolsa Família Programme (PBF) has over ten years of existence and, during this period, became the main income transfer programme of federal government that aims to fight poverty. In this context, the task performed by the municipal management of the programme seems to be relevant, since this is responsible for registering, guiding and monitoring the beneficiary families. Considering this, the central objective of this doctoral thesis is to understand the dynamics and relationships that occur in the 'end' of the municipal management of PBF in a large urban centerin the 2012 to 2015 period. The analysis focuses on the beneficiaries of the programme and their relationship with the social agents responsible for implementing this public policy. For this purpose, it was conducted an ethnographic research in a favela located in the south area of the city of Rio de Janeiro, noting especially the beneficiaries residents and the attendances in the Social Assistance Reference Center (CRAS) −one of the responsible entities for the implementation of the program at municipal level. It has been sought thereby to analyze the strategies and negotiations that arise from the relationship between the parties involved (beneficiaries and social workers), as well as the impact and significance of the benefit in consumption of families served by the programme residing in the favela. Among the results achieved, it is emphasized that, at the municipal level, in order to become or remain a beneficiary, there are strategies and 'informal' negotiations different from those established by the official guidelines of the programme and the beneficiaries attribute different meanings to the income.